Advancing Business Services Through Web and Mobile Application Development - Ahlul Aziz; Sri Wulandari (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2023)
Cafés are commercial establishments that serve food and drinks to customers in a casual setting. They also provide a conducive environment for relaxation and socializing with relatives. However, the operational processes of many cafés in Yogyakarta, including the Konogawa Coffee & Culture, still rely on manual methods, resulting in long queues and extended waiting times when multiple customers arrive simultaneously. To address these challenges and enhance service performance, a system comprising a mobile application and an interconnected website has been developed. The website serves as a promotional medium, providing information about the café, while the mobile application enables customers to conveniently place menu orders online. The system design incorporates API technology to establish seamless connectivity between the website and the mobile application. When a customer uses their mobile device connected to the local area network to place an order, the ordering information is promptly transmitted to the cashier, who then forwards it to the kitchen. By improving the delivery of order information, this system enhances service performance and reduces customer wait times.